Expanding the Remote Experiment Set with the 3Axis Portal Physical Model - Henke, Karsten; Nau, Johannes; Wuttke, Heinz-Dietrich; Poliakov, Mykhailo; Tabunshchyk, Galyna; Parkhomenko, Anzhelika; Poliakov, Oleksii (International Journal of Online and Biomedical Engineering (iJOE), 2022)
The problem of insufficient variety of experiments with physical models in laboratory workshops for distance learning in the design of control systems is posed. It is caused by the limited operations with the physical model when using the interface at the level of electromechanics control. The way of solving the problem is substantiated: the transition from electromechanics control of physical models of devices to control systems for the processes of using these devices. The proposed way to increase the number of types of experiments is illustrated with examples of systems for using popular physical models of an elevator, storage warehouse and production cell. However, the main focus is on expanding the functionality of the physical model 3-Axis Portal. These possibilities are realized by equipping the portal head of the base model with new sensors and actuators, improving the loads with which the portal works and using new types of active surfaces in the working field of the portal. Based on the aggregation of the proposed nodes with the basic portal model, sixteen types of systems for setting up remote experiments are described. The structures of these systems, elements of implementation and variants of experiments are described, which relate to the design of digital control systems, visualization of sorting algorithms, technical diagnostics of electronic assemblies, pattern recognition and other relevant topics for teaching students of engineering specialties.